2021
DOI: 10.1002/wer.1510
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of chromium(VI) removal by indigenous microalga (Chlamydomonas sp.)‐based biosorbent using response surface methodology

Abstract: Phycoremediation of heavy metals has garnered considerable recent research interest. In this study, an indigenous microalga (Chlamydomonas sp.)‐based biosorbent was employed for biosorption of Cr(VI) dissolved solids (Cr(VI)‐DS), optimized using response surface methodology (RSM). The effects of microalga concentration, pH, and contact time were studied with 250 mg Cr(VI)‐DS L−1. The biosorption of Cr(VI)‐DS was higher at acidic pH (94.17% at pH 4) than at alkaline conditions (68.53% at pH 10). The interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The correction determination coefficients R adj 2 of the two models were 0.9629 and 0.9750, respectively, indicating that 3.71 and 2.5% of the variance, respectively, could not be explained by the model. 31 The coefficients of variation were 0.67 and 0.89, respectively, which further indicated that the model was accurate and suitable for preliminary analysis and prediction of Cr(VI) and total chromium removal efficiency.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The correction determination coefficients R adj 2 of the two models were 0.9629 and 0.9750, respectively, indicating that 3.71 and 2.5% of the variance, respectively, could not be explained by the model. 31 The coefficients of variation were 0.67 and 0.89, respectively, which further indicated that the model was accurate and suitable for preliminary analysis and prediction of Cr(VI) and total chromium removal efficiency.…”
Section: Resultsmentioning
confidence: 74%
“…It can be seen from Tables and that the p values of the regression model of Cr­(VI) and total chromium removal efficiencies are both <0.0001, indicating that the model is extremely significant; p values of misfit terms are all >0.05, and it shows that the model fits well with the experiment, and the regression equation can be used to analyze the experimental results instead of the real points. The correction determination coefficients R adj 2 of the two models were 0.9629 and 0.9750, respectively, indicating that 3.71 and 2.5% of the variance, respectively, could not be explained by the model . The coefficients of variation were 0.67 and 0.89, respectively, which further indicated that the model was accurate and suitable for preliminary analysis and prediction of Cr­(VI) and total chromium removal efficiency.…”
Section: Resultsmentioning
confidence: 96%
“…However in another study using microalga Chlamydomonas sp., nearly 90% biosorption has been observed in 30 mins of contact time. [21]. Although various studies have have highlighted much more longer contact time to get maximum biosorption, studies by Zhang et.al showed that using a contact time of 60 mins using Bacillus subtilis, nearly 90% biosorption has been observed [22].…”
Section: Resultsmentioning
confidence: 99%
“…(92.89%) [65], higher than that by Planothidium lanceolatum (about 87%) [26], Chlamydomonas sp. (91.31%) [66], Scenedesmus quadricauda (47.6%) [67], and Chlorella vulgaris (43%) [41], and lower than that by Chlorella sorokiniana (99.67%) [68], and Scenedesmus quadricauda (98.1%) [69]. It is clear from the table above that this alga has high metal binding capacities.…”
Section: Optimization Of Cr(vi) Removal Conditions For C Subminusculamentioning
confidence: 89%